New Jensen’s Type Inequalities for Differentiable Log-Convex Functions of Selfadjoint Operators in Hilbert Spaces - Dragomir, S.S. (Sarajevo Journal of Mathematics, 2024)
Some new Jensen's type inequalities for differentiable log-convex functions of selfadjoint operators in Hilbert spaces under suitable assumptions for the involved operators are given. Applications for particular cases of interest are also provided. 2000 Mathematics Subject Classification. 47A63, 47A99